Agro-Communicative Networks Rural Sociology Perspectives on Knowledge Sharing and Innovation Diffusion in Sustainable Agriculture - Amalia, Artanindia Lailatul; A'zdom, Muhammad Khofidul (Professorline, 2025)
Sustainable agricultural transformation depends not only on technology but also on communication, trust, and collective participation. This study develops a conceptual framework of Agro-Communicative Networks by integrating insights from rural sociology and development communication. Drawing upon secondary data from the article “Communication and Social Capital in Community-Supported Agriculture” (JAFSCD, 2022) and supporting literature from 2015–2025, the study explores how communication processes contribute to the formation of social capital and the diffusion of innovation in rural agricultural systems. The analysis reveals that communication builds social capital through three interrelated mechanisms: bonding (trust and solidarity within groups), bridging (horizontal collaboration among communities), and linking (vertical connections with institutions). These communicative relationships generate collective learning and shared decision-making, which accelerate innovation diffusion and strengthen the sustainability of agricultural practices. The proposed Agro-Communicative Network Framework conceptualizes this dynamic as a continuous cycle in which dialogue fosters trust, trust builds social capital, and social capital enhances the quality and depth of future communication. The findings suggest that agricultural innovation should be understood as a socially negotiated process rather than a unidirectional transfer of knowledge. Strengthening participatory communication through local media, farmer cooperatives, and digital platforms can enhance community resilience, inclusivity, and long-term sustainability. The study concludes that communication is not only a medium of coordination but also a strategic driver of social innovation in the rural agribusiness ecosystem.